Reassessing the Economic Freedom–FDI Nexus: Evidence from ASEAN Economies - Imelda Kartika Surasman; Adwin Surja Atmadja; Mahdi Fahgani (Institute of Research and Community Outreach - Petra Christian University, 2025)
The latest literature reports that economic freedom is one of the increasingly significant factors influencing foreign direct investment (FDI). Nevertheless, most literature examines aggregate indices, leaving out the detailed effects of its individual components. Despite its growing role in global FDI flows, the ASEAN region has limited empirical evidence. The study addresses this gap by examining five areas of the Fraser Institute’s economic freedom effects on FDI inflows in ASEAN economies from 2010 to 2022. Employing panel data regression, the analysis finds that some areas show significant impacts on FDI, while others do not. The findings underline the importance of distinguishing among the areas when assessing the drivers of foreign investment. These results offer insights for regulators seeking to improve the country’s investment climate through reforms focused on strengthening economic governance and institutional quality.